2012
DOI: 10.1002/pssa.201200037
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt out‐diffusion and carbon phase composition at the WC‐10%Co/diamond film interface investigated by XPS, SEM, Raman and SIMS

Abstract: The effect of cobalt out‐diffusion from the WC‐10%Co/diamond film interface towards the diamond film surface, in terms of carbon phase, chemical composition and dependence of pre‐treatment for enhancement of diamond formation was investigated. Diamond films of various thicknesses were deposited onto substrates pre‐treated by a dual step process consisting of carburization and subsequently diamond seeding or just diamond seeding. Our findings show that the dual step pre‐treatment promotes diamond formation at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In our previous studies, we found that a ∼1.5 μm Cr–N thickness interlayer enhanced the adhesion of diamond films deposited on WC–Co substrates . This was due to a number of effects: (i) prevention of diffusion of Co from the substrate into the diamond film, which hinders the catalytic activity of Co; (ii) formation of a few nm thick Cr–C interface between the interlayer and the diamond film, which enhances chemical adhesion of the films to the interlayer; and (iii) a “net‐like” microstructure of the Cr–N interlayer, which provides a mechanical adhesion by “anchoring effect.”…”
Section: Introductionmentioning
confidence: 92%
“…In our previous studies, we found that a ∼1.5 μm Cr–N thickness interlayer enhanced the adhesion of diamond films deposited on WC–Co substrates . This was due to a number of effects: (i) prevention of diffusion of Co from the substrate into the diamond film, which hinders the catalytic activity of Co; (ii) formation of a few nm thick Cr–C interface between the interlayer and the diamond film, which enhances chemical adhesion of the films to the interlayer; and (iii) a “net‐like” microstructure of the Cr–N interlayer, which provides a mechanical adhesion by “anchoring effect.”…”
Section: Introductionmentioning
confidence: 92%
“…This is because Co in WC-Co interlayer evaporated under high temperature and low pressure condition. At high deposition temperatures, ball-shaped cobalt particles will form on the surface of the sample and can move during diamond deposition [35] . Also, when diamond film was depositing, a small fraction of Co on the surface of interlayer diffused to the surface of diamond through defects such as grain boundaries and cracks.…”
Section: Near Surfacementioning
confidence: 99%
“…The specific structure of the Co-rich particles on the plasma nitrided surface suggests that N in the Co 4 N layer diffuses outward during HFCVD. These released N atoms react with carbon atoms absorbed on the surface; thus, it probably prevents catalytic graphitization of γ-Co [41,43]. This promotes the formation of diamond nuclei at the interface.…”
Section: Effect Of the Conversion Layer On Hfcvdmentioning
confidence: 99%